The influence of socioeconomic status on job and life satisfaction among low-income employees in Johor Local Authorities - Kamalulil, Errna Nadhirah Binti; Panatik, Siti Aisyah Binti; Sarwar, Farhan (Faculty of Psychology and Health - Universitas Islam Negeri Walisongo Semarang, 2021)
Many studies have found that a low socioeconomic status has a negative impact on welfare. However, contextual evidence on this issue in Malaysia is scarce. Therefore, this study attempts to quantitatively examine the effect of socioeconomic status on life and job satisfaction among low-income employees working in the public. The Satisfaction with Life Scale (SWLS), Work Domain Satisfaction Scale (WDSS), and Socioeconomic Questionnaire were presented to 265 respondents chosen using a convenience sampling technique. The data were then analyzed using SPSS 26.0 and SmartPLS 3.0 equation modeling. The results show that socioeconomic status had a positive effect on life satisfaction (t = 4.581; p < .001) and job satisfaction (t = 3.423; p < .001). Thus, this study contributes to the provision of better insights into the socioeconomic status factors that determine life and job satisfaction, especially among low-income employees working in the public sector in Malaysia.